ISI POMPASI İLE SICAK SU ÜRETİMİ VE ELEKTRİKLİ TERMOSİFONLA MUKAYESESİ - BOZKIR, OĞUZ (Fırat Üniveristesi, 1994)
Yüksele Lisans Tezi ISI POMPASI İLE SICAK SU ÜRETİMİ VE ELEKTRİKLİ TERMOSİFONLA MUKAYESESİ Oğuz BOZKIR Fırat Üniversitesi Fan Bilimleri, Enstitüsü Makina Mühendisliği Anabilim Dalı 1994 Bu çalışmada, konutların ihtiyacı olan sıcak suyun ısı pompası ile üretimi incelenmiş ve halen yaygın olarak kullanılmakta olan elektrikli termosifonlarla mukayesesi yapılmıştır. Isı pompası çevrimi önce teorik olarak incelenmiş, sonra Hava-su tipi bir ısı pompasının tasarımı yapılarak, 401 sıcak su üretebilecek kapasitede bir deney seti kurul muştur. Soğutucu akışkan olarak Freon-22 kullanılarak yapılan deneylerde sistemin ısıtma tesir katsayısı (C.O.P) tesbit edilmiş, enerji tüketimi bakımından elektrikli ter mosifonlarla mukayesesi yapılmıştır. ANAHTAR KELİMELER: Isı pompası, soğutucu akışkan, ısıtma tesir katsayısı, Freon-22

SUMMARY Masters Thesis PRODUCING HOT WATER BY MEANS OF A HEAT PUMP AND COMPARING IT WITH AN ELECTRICAL HEATER Oğuz BOZKIR Fırat University Graduate School of Natural and Applied Science: Department of Mechanical Engineering 1994 In this study producing domestic hot wa-ter foy means of an air to water type heat pump system was researched and compared with an electrical heater which is commonly used. For experimental studies a heat pump system which is able to produce 40 It hot water was installed. It was used Freon-22 for refrigerant in heat pump system. After the experiments coefficient of performance for heat pump system was defined. Finally, the heat pump system was compared with the electrical heater KEY WORDS: Air to water type heat pump, Refrigerant, Freon-22, Coefficient of performance.
Producing hot water by means of a heat pump and comparing it with an electrical heater
Keywords: Makine Mühendisliği; Mechanical Engineering